Zoomorphic metaphor in the phraseology of the Belarusian and English languages (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2017)
The article raises the theoretical question of zoomorphic metaphor as a method of the linguistic characteristics of a human and as a fragment of the national language worldview. The object of research within the article is the phraseological units with a zoonymiccomponent crow in the Belarusian and English languages. Based on the material of selected phraseological units metaphorical roots of image creation are derived, universal and unique features in the use of the process of metaphorization and the methods of naming, in the views and assessments of the Belarusians and the Britishabout the selected bird for characterization and evaluation of person are revealed.Based on the analysis of inner form and meaning of phraseological units, common and distinctive features (objective and subjective) and characteristics that form the cultural and linguistic image of crow in the phraseological worldview of the Belarusians and the British are defined. Two common features ‘a crow is a bad creation’ and ‘a crow can be white’ for the two languages are revealed, though each language has its own associations and ideas. Thus in the basis of images of English phraseological units, unlike in Belarusian ones, other objective associative features are put that describe the natural characteristics of crow. The paper also reveals that the zoomorphism crow in the phraseological worldview of the Belarusians and the British contains a projection on a person or objects of reality (material or abstract), hence there are the metaphorical signs “a crow is a man” and “a crow is an abstract notion / thing”. The metaphorical sign “a crow is a man” has a predominantly negative connotation – the component crow replaces a person endowed with negative characteristics. The negative image of a crow in the perception of two societies is explained by the “dark” symbols of the image of this bird. However, the Belarusians and the British negatively perceive and evaluate the crow by different marks.In general, the figurative meanings of zoomorphism crow in phraseological units of the Belarusian and English languages are determined by the traditional views of the native speakers of two cultures.
Keywords: zoomorphic metaphor; zoomorphism; association; image; component; inner form